Las izquierdas en el gobierno. Políticas sociales en América Latina (2000-2015) (The Left in Government Social. Policies in Latin America (2000-2016)) (Emancipação, 2018)
At the end of the last century the application of the neoliberal recipe book in Latin America left behind a sequel of negative consequences. It is at the beginning of the present century that successive electoral victories of the left parties or center-left are registered, giving rise to a process of transformations that - although gradual and partial - has implied the strategic, programmatic and normative reorientation of the social policies. Three factors were fundamental and largely explain this process; in the first place, the coming to power of the left or progressive forces (ideological key), secondly, social mobilization (collective action key), and third, the good performance of local economies measured in sustained growth rates of GDP - Gross Domestic Product (economic key). Based on these factors, we identify some of the common characteristics of social policies, the successes and the impacts generated, as well as the insufficiencies and limitations of the model.
Keywords: social policies, welfare, democracy